Persistent patriarchy: theories of race and gender in science - Sur, Abha (2008)
The relationship between science and social inequality is the subject of an ongoing debate. This paper argues in favour of a philosophy of science, which is alert to its democratic potential but does not simultaneously bury the historical - and continuing - role of science in legitimising racial, gender, and class/caste discrimination. - Reproduced.
Keywords: Women in science